Peningkatan Literasi Kebencanaan Siswa Berbasis Data Geospasial - Rusiyah, Rusiyah; Nurfaika, Nurfaika; Melo, Ramla Hartini; Massi, Silva; Mokodompit, Mohamad Alfarezy; Agu, Rahmat Rafly (-, 2025)
Disaster literacy is a crucial aspect for the people of Gorontalo, as the region is highly vulnerable to various natural hazards. This program aimed to enhance students’ disaster literacy through geospatial data-based learning. The program was conducted at SMAS Wira Bhakti Gorontalo with 20 students as participants. The activities were carried out in several stages: preparation, pretest, lecture, training (hands-on), posttest, and reflection. The results of the pretest and posttest showed an improvement in students’ knowledge. The average pretest score of 67 increased to 88 in the posttest. This finding indicates that the use of geospatial data is effective in improving students’ understanding of disasters. Reflections and student responses further revealed that this program was beneficial in enhancing students’ preparedness for disasters. This program successfully improved students’ disaster literacy and contributed to fostering a disaster-resilient young generation.